A BIBLIOMETRIC ANALYSIS OF PLATFORM RESEARCH IN E-COMMERCE: PAST, PRESENT, AND FUTURE RESEARCH AGENDA - Wulfert, Tobias; Karger, Erik (Corporate Ownership & Control, 2022)
An important economic sector influenced by the development of platforms is e-commerce. The most successful companies in e-commerce employ platform business models and strive to provide other companies with application services. Despite growing economic importance and rising research interest, thus far, no attempts were made to structure existing research into platforms in e-commerce. Hence, a quantitative bibliometric analysis of 7,463 platform-related papers in the context of e-commerce was conducted. The papers were published in major conferences, journals, and books from 1993 to 2021. The authors identified a continuous development of platform research in e-commerce, with the continuous development characterized by three major periods of research. Furthermore, four clusters in platform research are outlined, i.e., business models, social commerce, infrastructure, and socio-technical characteristics. These clusters can serve as a foundation for future research. The conducted bibliometric analysis contributes to scientific research by offering an objective and systematic overview of platform research in e-commerce.